Formation and evolution of the modem warm current system in the East China Sea and the Yellow Sea since the last deglaciation - 李铁刚 南青云 江波 孙荣涛 张德玉 李青 (Chinese journal of oceanology and limnology, 2009)
To reconstruct the formation and evolution process of the warm current system within the East China Sea （ECS） and the Yellow Sea （YS） since the last deglaciation, the paleoceangraphic records in core DGKS9603, core CSH1 and core YSDP102, which were retrieved from the mainstream of the Kuroshio Current （KC）, the edge of the modern Tsushima Warm Current （TWC） and muddy region under cold waters accreted with the Yellow Sea Warm Current （YSWC） respectively, were synthetically analyzed. The results indicate that the formation and evolution of the modern warm current system in the ECS and the YS has been accompanied by the development of the KC and impulse rising of the sea level since the last deglaciation. The influence of the KC on the Okinawa Trough had enhanced since 16 cal kyr BP, and synchronously the modern TWC began to develop with the rising of sea level and finally formed at about 8.5 cal kyr BP. The KC had experienced two weakening process during the Heinrich event 1 and the Younger Drays event from 16 to 8.5 cal kyr BP. The period of 7-6 cal kyr BP was the strongest stage of the KC and the TWC since the last deglaciation. The YSWC has appeared at about 6.4 cal kyr BE Thus the warm current system of the ECS and the YS has ultimately formed. The weakness of the KC, indicated by the occurrence of Pulleniatina minimum event （PME） during the period from 5.3 to 2.8 cal kyr BE caused the main stream of the TWC to shift eastward to the Pacific Ocean around about 3 cal kyr BE The process resulted in the intruding of continent shelf cold water mass with rich nutrients. Synchronously, the strength of the YSWC was relatively weak and the related cold water body was active at the early-mid stage of its appearance against the PME background, which resulted in the quick formation of muddy deposit system in the southeastern YS. The strength of the warm current system in the ECS and the YS has enhanced evidently, and approached to the modern condition gradually since 3 cal kyr BE